RANCANG BANGUN UNIT PENGENDALI KETINGGIAN AIR DALAM TANDON - Widiasih, Wiwin; Murnawan, Hery (Heuristic, 2016)
In order to always meet their daily needs, the amount of water in the reservoir mustalways be maintained, which shall not be less than the minimum and not higher than themaximum limit. Thereby filling reservoir must be controlled. From the number of unitscontrolling water level in the reservoir turns encountered many disadvantages. Thisstudy aimed to innovate controller unit as perfecting the control unit that had beenthere. The control unit is designed to use a water level sensor. With SWOT analysis andLikert scale analysis eventually showed that the new control unit has a goodperformance and can be accepted by the public.Key Words: innovation, control, swot, Likert